Pengaruh Konsumsi Jantung Pisang Terhadap Peningkatan Produksi Asi : Studi Kasus - Intan Yusita; Hani Oktafiani; Cici Valiani; Pratiwi Swastika; Meda Yuliani (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Smooth milk production is one of the factor that can affect breastfeeding for babies. The better the nutricion consumed by the mother, the more milk production will increase. Banana heart contains laktogagum which can increase the smooth production of breast milk. To determine the effectiveness of giving Banana heart to increase the smooth production of breastmilk ini Pagarsih Health Center. This study uses a case study (case study) descriptively with midwifery care continuously of care.The result of the care provided were in accordance with the theory and giving Banana heart to postpartum mothers for 7 days was effective to increase the smooth production of breast milk. Giving Banana heart is effective to increase the smooth production of breast milk. Giving Banana heart is effective to increase the smooth production of breast milk.